Pengaruh Dimensi Kecerdasan Emosional Terhadap Kinerja Pegawai Pada Badan Penelitian dan Pengembangan Daerah (Balitbangda) Provinsi Sulawesi Selatan - Zaitun, Cakra; Jannah, Miftahul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The objectives of this research are: (1) to find out and analyze the influence of emotional intelligence dimensions in terms of self-awareness, self-regulation, self-motivation, empathy, and social skills to the work performance of employees of Balitbangda Provinsi Sulawesi Selatan and (2) to find out and analyze which emotional intelligence dimension that is most dominant in influencing the work performance of employees of Balitbangda Provinsi Sulawesi Selatan. The research was conducted in Badan Penelitian dan Pengembangan Daerah (Balitbangda) Provinsi Sulawesi Selatan with a population of 51 employees as the respondents. The data analysis is used to descriptively explain the characteristics of respondents and the description of the research, whereas Regresi Berganda analysis tool is used to analyze the quantitative data. This research examines the influence of emotional intelligence dimensions to the work performance enhancement of the employees. The result shows that the value of R, R2 and average R2 give significant influence. Regression coefficient (B) for self-awareness variable (X1), self-regulation (X2), self-motivation (X3), empathy (X4), and social skills (X5), and also regression coefficient constant give significant influence. It turns out that self- awareness variable (X1) becomes the most dominant variable that influences the work performance enhancement of employees of Balitbangda Provinsi Sulawesi Selatan. The result of this research suggests the employees of Balitbangda Provinsi Sulawesi Selatan to always implement the emotional intelligence dimensions in daily life, and improve their emotional intelligence as well.